Diagnostic value of plain abdominal radiographs in patients with acute abdominal pain - Prasannan, Subhita; Tam, Jenn Zhueng; Alif Gul, Yunus Gul (Elsevier, 2005)
Objective: A prospective study was performed over a 3-month period in a tertiary referral centre to evaluate the appropriateness and contribution of plain abdominal radiographs (PAR) in the diagnosis and management of adult patients presenting with acute abdominal pain. Methods: Forward stepwise logistic regression was used to examine the correlation between PAR findings and the final diagnosis. The Chi-squared test was used to determine any changes in patient management including requirement for surgical intervention based on PAR findings (p < 0.05). Results: Of 168 patients (246 PAR), 59 (35%) had positive findings on PAR. PAR were most sensitive in cases of intestinal obstruction (odds ratio, OR = 33.548, r = 0.561). The sensitivity was further increased if three of the following predictive signs were present: exaggerated bowel sounds (OR = 13.350, r = 0.154), abdominal distension (OR = 2.993, r = 0.234) and age over 50 years (OR = 2.301, r = 0.027). PAR were non-diagnostic in 82% of patients with acute abdominal pain (p < 0.001). Conclusion: PAR do not play a major role in influencing the management of patients with acute abdominal pain without coexisting bowel obstruction.